Digital Work Resources and Innovative Work Behaviour in Small and Medium-Sized Enterprises: The Mediating Role of Digital Engagement - Haryadi Sumarsono; Rosyana Nashir; Taufiq Sugiarto (CV. Vocezmi Learnov, 2026)
This study investigates the relationship between digital work resources and innovative work behaviour in small and medium-sized enterprises (SMEs), examining the mediating role of digital engagement. Using a quantitative approach, data were collected from 60 SME owners and employees actively using digital technologies in East Java. Partial Least Squares–Structural Equation Modelling (PLS-SEM) was applied using SmartPLS and SPSS. The study reveals that digital work resources do not directly influence innovative work behaviour. Instead, digital engagement fully mediates this relationship, extending SME and digital work literature by emphasising engagement as a critical mechanism through which digital resources translate into innovation. The findings highlight that investments in digital technologies must be accompanied by strategies that enhance digital engagement, such as capability development and participative digital practices, to foster innovation in SMEs. The limited sample size and regional focus constrain generalisability. Future research should adopt broader samples, comparative settings, or longitudinal designs to further examine digital engagement dynamics in SMEs.